The increasing use of cosmetic non-ionising radiation applications - types of procedures, potential risks to consumers and regulation in Australia - Ken K Karipidis; David Urban; Rick A Tinker; Trevor Wheatley (Sax Institute, 2023)
In recent years, there has been a large increase in cosmetic applications using non-ionising radiation (NIR). These applications use various types of NIR such as lasers and ultrasound for numerous cosmetic outcomes such as epilation, skin rejuvenation and tattoo removal. Cosmetic NIR procedures are marketed as a low-cost and low-risk alternative to more invasive procedures. However, treatments with these devices always result in high NIR exposure to targeted tissue in order to ensure efficacy of treatment. Consequently, there is always a risk of adverse health effects from these procedures, which may be temporary or longer lasting. Research on the health risks of cosmetic NIR applications is lacking, particularly on the extent of poor treatment application or misuse. In Australia, except for the banning of solaria, there is no national regulation for the use of NIR devices for cosmetic purposes and only three states have established regulatory controls for certain optical cosmetic applications. To mitigate the impacts of this gap in oversight, the Australian Radiation Protection and Nuclear Safety Agency has published national advice for consumers and service providers that give information on cosmetic NIR treatments and the potential risks involved.